Bangkit Saja atau Sudah Berkembang: Perbandingan Resiliensi Pada Mahasiswa - Aprezo Pardodi Maba (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2018)
Resiliency is a term to define about someone situation who has ability to bounce back ofter depressing psychological event. This research is describing and comparing between South Sumatera student and Lampung student resilience. It using analitical device concerning brief resilience scale (Smith et al., 2008). Toward analytical data engaging descriptive quantitative and T-Test to find out the differences between two samples. And The results showing that the score of Sig (2-tailed) 0,054 > 0,05 which means no differences between South Sumatra and Lampung students, however the resilience average of Lampung is higher than South Sumatera students